New buffer layer for high-temperature superconducting ceramics on sapphire: LaBa2Cu3Oy/Ag bilayers - Nakamura, O. (1991)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of California; Estados Unidos